2016
DOI: 10.1007/5584_2016_163
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Assessment of Pneumonia Caused by Gram-Negative Bacteria in Patients Hospitalized in Intensive Care Unit

Abstract: The article presents the results of 11-year study (2005-2015) of Gram-negative bacteria responsible for pneumonia in 2033 mechanically ventilated patients hospitalized in Intensive Care Unit. Of 8796 biological samples, consisting mainly of bronchial aspirate (97.9 %), 2056 bacterial strains were isolated and subjected to identification. VITEK 2 was used to determine drug susceptibility (classified according to the EUCAST criteria). ESBL, MBL and KPC-producing strains were identified by means of phenotypic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Several recent studies have reported an elevated prevalence of GNB in nosocomial pneumonia, ranging from 25% in Poland up to 85% in Europe and in the US (Table ). Different microorganisms have been described as the most frequent ones.…”
Section: Mdr‐gnb In Nosocomial Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent studies have reported an elevated prevalence of GNB in nosocomial pneumonia, ranging from 25% in Poland up to 85% in Europe and in the US (Table ). Different microorganisms have been described as the most frequent ones.…”
Section: Mdr‐gnb In Nosocomial Pneumoniamentioning
confidence: 99%
“…Other studies described a higher isolation of Enterobacteriaceae among patients with nosocomial pneumonia. Guzek et al . evaluated retrospectively more than 2000 patients with VAP and positive bacterial cultures in Poland and showed a high prevalence of Enterobacteriaceae (42%), with an incidence of ESBL of 26%.…”
Section: Mdr‐gnb In Nosocomial Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The etiology of VAP pathogens are changing over the past years, therefore early detection of pathogens and knowledge of sensitivity patterns are very crucial for better patient outcomes [ 5 ]. There is an increasing evidence of emergence of multidrug‑resistant (MDR) pathogens due to extended spectrum beta (β)-lactamases (ESBL), AmpC β-lactamases (AmpC) or metallo-β-lactamases (MBLs) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 34.15% of the CARB R isolates were characterized as VIM-2 producers which were identified exclusively from patients from Pneumology and ICUs in H2 (Table S1). The bacterium is known to colonize the lungs of patients with Cystic Fibrosis with highly resistant VIM-2 isolates [43], but it is also widespread in patients with other respiratory problems [44][45][46]. The isolation of MDR/VIM-2 strains from sputum and bronchial secretions during the present study was not surprising, although it was the first time that the P. aeruginosa population of H2 was tested for MBL production.…”
Section: Discussionmentioning
confidence: 65%